A comparison of the badminton split and cut movement with a plant and cut movement - Reeves, J.; Trewartha, G.; Churchill, S. M. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Introduction: The plant and cut is an established mechanism for non-contact anterior cruciate ligament (ACL) injury as it involves multiplanar motion that likely places greater strain on the ACL than sagittal motion alone (Markolf et al, 1995, Cochrane et al, 2007). Badminton players perform cutting like movements that may place them at a high risk of ACL injury (Kimura et al, 2010). The aim of this study was to compare knee joint moment patterns of a standard plant and cut with a badminton-specific split and cut movement. Methods: Eight healthy, experienced, female badminton players (23 ± 6 years) performed badminton movements and cutting movements. Badminton movements started with a split step followed by a cut and a mimicked forehand or backhand shot, while cutting movements were a plant and cut or crossover from a running start. Ground reaction forces and three-dimensional kinematics were combined in order to calculate internal knee joint moments using inverse dynamic analysis. Results: Mean peak extension moment of the lunge leg was 1.21-1.40 N•m/kg/m, mean peak abduction/adduction moment was -0.36--0.41 N•m/kg/m and mean peak internal rotation moment was 0.21-0.41 N•m/kg/m. Mean peak internal rotation moment of the lunge leg in the forehand (0.41 ±0.06 N•m/kg/m), was significantly greater than the lunge leg of the backhand (0.21 ±0.03 N•m/kg/m), significantly greater than the propulsive leg of the forehand (0.10 ±0.18 N•m/kg/m), but not significantly different to the leg that makes the step after the cut in the plant and cut (0.43 ±0.13 N•m/kg/m). Discussion: Knee joint loading in both forehand and backhand movements occurred in multiple planes and was similar to the high risk plant and cut movement. The peak internal rotation moment of the lunge leg during the forehand movement, in combination with loading in other planes, was of a level that could place a considerable load on the knee joint ligaments (Besier et al, 2001), This could partly explain the ACL injuries to the racket-hand side knee during the forehand plant and cut shot reported by Kimura et al, (2010). An important difference between the cutting movements in team sports and badminton may be that the push-off leg is the leg that is typically injured in the plant and cut and crossover (Cochrane et al, 2007), but the lunge leg experiences greater loading in cut movements in badminton. Therefore, findings in the literature regarding planting and cutting may not be directly transferable to badminton movements.